How Heme Oxygenase-1 Prevents Heme-Induced Cell Death. - Lilibeth Lanceta; Jacob M Mattingly; Chi Li; John W Eaton (PLoS ONE, 2015)
Earlier observations indicate that free heme is selectively toxic to cells lacking heme oxygenase-1 (HO-1) but how this enzyme prevents heme toxicity remains unexplained. Here, using A549 (human lung cancer) and immortalized human bronchial epithelial cells incubated with exogenous heme, we find knock-down of HO-1 using siRNA does promote the accumulation of cell-associated heme and heme-induced cell death. However, it appears that the toxic effects of heme are exerted by "loose" (probably intralysosomal) iron because cytotoxic effects of heme are lessened by pre-incubation of HO-1 deficient cells with desferrioxamine (which localizes preferentially in the lysosomal compartment). Desferrioxamine also decreases lysosomal rupture promoted by intracellularly generated hydrogen peroxide. Supporting the importance of endogenous oxidant production, both chemical and siRNA inhibition of catalase activity predisposes HO-1 deficient cells to heme-mediated killing. Importantly, it appears that HO-1 deficiency somehow blocks the induction of ferritin; control cells exposed to heme show ~10-fold increases in ferritin heavy chain expression whereas in heme-exposed HO-1 deficient cells ferritin expression is unchanged. Finally, overexpression of ferritin H chain in HO-1 deficient cells completely prevents heme-induced cytotoxicity. Although two other products of HO-1 activity--CO and bilirubin--have been invoked to explain HO-1-mediated cytoprotection, we conclude that, at least in this experimental system, HO-1 activity triggers the induction of ferritin and the latter is actually responsible for the cytoprotective effects of HO-1 activity.